Torsion of an Accessory Spleen in a Child With Biliary Atresia Splenic Malformation Syndrome - Simon, David A.; Fleishman, Nathan R.; Choi, Pamala; Fraser, Jason D.; Fischer, Ryan T. (Frontiers in Pediatrics, 2020)
Torsion of an accessory spleen is an exceedingly rare cause of abdominal pain in pediatric patients. The diagnosis is frequently challenging as presentation is variable and diagnostic imaging can be aspecific. The current case describes an unusual presentation of a torted accessory spleen in a 5-year-old girl with biliary atresia splenic malformation syndrome who initially presented with non-specific abdominal symptoms and fever. The diagnosis was made following fine-needle aspiration of a suspected intraabdominal abscess. The case highlights the diagnostic challenge of accessory splenic torsion and stresses the importance of its inclusion on the differential diagnosis of pediatric patients, especially those with known splenic or laterality abnormalities, presenting with both acute and sub-acute abdominal symptoms.